Place the Logo High or Low? Using Conceptual Metaphors of Power in Packaging Design. (September 2014) - Sundar, Aparna; Noseworthy, Theodore J.
Across three studies, this research examines how marketers can capitalize on their brand's standing in the marketplace through strategic logo placement on their packaging. Using a conceptual metaphor framework, the authors find that consumers prefer powerful brands more when the brand logo is featured high rather than low on the brand's packaging, whereas they prefer less powerful brands more when the brand logo is featured low rather than high on the brand's packaging. Furthermore, the authors confirm that the underlying mechanism for this shift in preference is a fluency effect derived from consumers intuitively linking the concept of power with height. Given this finding, the authors then demonstrate an important boundary condition by varying a person's state of power to be at odds with the metaphoric link. The results demonstrate when and how marketers can capitalize on consumers' latent associations through package design.